Diagnostic Sensitivity of the McMaster Technique for Detecting Intestinal Parasites in Human Populations: A Systematic Review and Meta-Analysis - Jurairat Jongthawin; Aongart Mahittikorn; Kinley Wangdi; Frederick Ramirez Masangkay; Manas Kotepui (Tropical Medicine and Infectious Disease, 2026)
Intestinal parasitic infections, particularly soil-transmitted helminths (STHs), remain a major public health concern in low- and middle-income countries. As control programs reduce infection intensity, accurate diagnosis becomes increasingly challenging. The McMaster technique has been proposed as an alternative diagnostic method for detecting human intestinal parasites; however, its diagnostic performance in human populations remains unclear. This study aimed to evaluate the diagnostic sensitivity of the McMaster technique for detecting intestinal parasites, particularly STHs. A systematic review and meta-analysis were conducted in accordance with the PRISMA guidelines and registered in PROSPERO (CRD420261298952). Electronic databases (PubMed, Scopus, Web of Science, Ovid, Nursing & Allied Health Premium, and Google Scholar) were searched up to January 2026. Studies assessing the McMaster technique in human populations and reporting sufficient data to calculate sensitivity were included. A random-effects model was used to estimate pooled sensitivity, with subgroup analyses by parasite species, geographic region, and population characteristics. Risk of bias was assessed using the the Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) tool. Among the 1514 records identified through database searching, 10 studies were included in the final analysis. The pooled sensitivity of the McMaster technique was 73% (95% confidence interval [CI]: 67–78%; I2 = 91.0%) for detecting any intestinal parasites and 72% (95% CI: 65–78%; I2 = 93.5%) for STHs. Species-specific sensitivities were 67% (95% CI: 61–72%; I2 = 80.7%) for Ascaris lumbricoides, 79% (95% CI: 57–91%; I2 = 96.9%) for Trichuris trichiura, and 71% (95% CI: 61–80%; I2 = 89.9%) for hookworms. The McMaster technique demonstrates moderate sensitivity for detecting intestinal parasites in humans. While it offers practical advantages for field applications, its reduced sensitivity in low-intensity infections limits its utility as a standalone diagnostic tool in control and elimination settings. Further research should focus on methodological standardization and integration with more sensitive diagnostic approaches.